ICE manual of blue-green infrastructure - Washbourne, Carla-Leanne; Wansbury, Claire (ICE manuals, 2023)
ICE Manual of Blue-Green Infrastructure draws together an exceptional breadth of material to provide a complete practical reference on Blue-Green Infrastructure (BGI) solutions. Written and edited by leading specialists, each chapter provides a contemporary overview of a significant area within the field and guidance on key considerations in BGI design, creation, retrofitting and maintenance. The book will help practitioners to explain the value of BGI, embed it into new development projects, retrofit it to older ones and provide for its long-term successful maintenance.